PEMANFAATAN EMPING MELINJO MENJADI OLAHAN EMPING MADU DALAM MENINGKATKAN EKONOMI MASYARAKAT DUSUN MAKAMDOWO - Habibi Hidayat; Unggul Priyadi; Tatwam Widi; Mochammad Iqbal S; Muhammad Saifudin; Nicolaz Arif F; Luthfi Ali Masykur; Kharisma Wijayanti; Bella Atika Armalinda; Annisa Ayunda Permata S; An’nisa Lutfi Nur A (DHARMA BAKTI, 2020)
Makamdowo Hamlet is a hamlet located in Sidomulyo Village, Purworejo District, Purworejo Regency, Central Java. Sidomulyo Village 70% its territory is contoured in hills and 30% of its territory is plain (rice fields). Most of the people in the Makamdowo Hamlet work as laborers and farmers, and some also have small businesses such as emping melinjo, salted eggs, bamboo handicrafts, snacks, and also palm sugar. From these products, most people in Makamdowo Hamlet produce chips from melinjo. Emping melinjo producers only market their products in stalls around Sidomulyo Village and Makamdowo Hamlet or markets around Purworejo. Emping melinjo has the potential to be processed as chips like melinjo chips, besides that to have a higher selling value, the melinjo chips are processed products, namely honey cheese emping. Processed emping into honey cheese emping are processed products of innovation in the creative economy industry that have great opportunities to be traded or can even become superior products originating from Makamdowo Hamlet.